Effects of Intercropping ‘Orange-Fleshed’ Sweetpotato with Onion on the Level of Weevil Damage - Kapalamula, C. (2014)
The problem of household food and economic insecurity i.e. inability of families to produce and purchase enough food to meet basic needs is considered to be a major determinate of Malawi’s nutrition problems. The major nutritional disorder in Malawi is Vitamin A deficiency. Orange-fleshed sweetpotato (Ipomea batatas) was introduced through the program “Rooting out hunger in Malawi with nutritious orange-flesh sweetpotato” to combat Vitamin A deficiency in addition to providing the daily calorie requirement. Production of sweetpotato is however challenged by the sweetpotato weevil damages and rotting problems. Unavailability of acceptable improved varieties, high incidence of pests and diseases, and poor cultural practices are also the main causes of low yields. A field experiment was carried out in Dedza (Malawi) from April to November 2013 to assess the “effects of intercropping orange-fleshed sweetpotato with onion on the level of weevil damage” with the objectives of developing a biological efficient onion intercropping for orange-fleshed sweetpotato (OFSP) production and determining the agronomic productivity of the intercrop systems. The experiment was conducted in a Randomized Complete Block Design (RCBD) with four treatments; sole cropped OFSP and Onion, and OFSP+Onion intercropped at ratios 2:1 and 4:1 respectively.